Organizational Culture and Sustainability in the Context of Higher Education Institutions: A Bibliometric Study - Cruz-Cárdenas, Jorge (2023)
Sustainability is of great importance for current and future societies, and higher education institutions (HEIs) play a leading role in sustainability efforts. Because organizational culture is a determining force in the success or failure of such efforts, this study examines the relationship between HEIs’ organizational cultures and their sustainability efforts. The research took a bibliometric approach and selected 594 relevant documents from the Scopus database. The descriptive analysis reveals a rapid growth in the rate of document publication that accelerates from the year 2015. At the level of both research and financial institutions that fund related research, most are linked to developed and emerging countries. An analysis of the co-occurrence of terms yielded four thematic clusters: (1) teaching and sustainability, (2) organizational and cultural change, (3) impacts of sustainability efforts, and (4) sustainability planning. From a dynamic perspective, the research emphasis has shifted from plans and projects to actors in university communities and their skills and knowledge.